Pengembangan Sumber Daya Manusia Berbasis Manajemen Strategis Pesantren (Studi terhadap Pondok Pesantren Tahfidzil Qur’an Al-Asror Bangkalan) - Qori, Imam; Basiran, Basiran; Faisol, Faisol (EL-BANAT: Jurnal Pemikiran dan Pendidikan Islam, 2023)
This research was carried out at the Tahfizul Qur'an Al-Asror Bangkalan Islamic Boarding School which implements 4 educational strategies in producing quality human resources, namely an Al-Qur'an-based curriculum, Amtsilati, formal schools and training. The aim of this research is to describe the formulation, implementation and evaluation of educational development strategies in producing quality human resources as a new paradigm in organizational management. This research use desciptive qualitative approach. The research results show: (1) the strategy formulation was developed based on Al-Asror's objectives, carrying out an independent organizational assessment. External environmental assessment by analyzing program needs, opportunities and strengths. Meanwhile, determining the strategy takes the form of direct instructions from the caregiver or the results of an agreement. (2) Islamic boarding school funds come from syahriyah, donors, cooperatives, infaq and caregivers. The program is implemented in a centralized, classical and specialization manner, either daily, weekly, monthly or annually and is guided by caregivers, administrators, asatidz and santri. (3) program evaluation by looking at the journal of students' activity and achievements. Improvements by providing motivation, creating alternative strategies, revising the structure or temporarily deactivating the program. There are 2 influencing factors, namely internal factors and external factors